Evaluation of pH, calcium ion release and antimicrobial activity of a new calcium aluminate cement - Fernanda de Carvalho Panzeri Pires-; Paola Castro Moraes; Lucas da Fonseca Roberti Garcia; Fabiano Gamero Aguilar; Evandro Watanabe (Sociedade Brasileira de Pesquisa Odontológica, 2013)
This study evaluated the pH, calcium ion release and antimicrobial activity of EndoBinder (EB), containing different radiopacifiers: bismuth oxide (Bi2O3), zinc oxide (ZnO) or zirconium oxide (ZrO2), in comparison to MTA. For pH and calcium ion release tests, 5 specimens per group (n = 5) were immersed into 10 mL of distilled and deionized water at 37°C. After 2, 4, 12, 24, 48 h; 7, 14 and 28 days, the pH was measured and calcium ion release quantified in an atomic absorption spectrophotometer. For antimicrobial activity, the cements were tested against S. aureus, E. coli, E. faecalis and C. albicans, in triplicate. MTA presented higher values for pH and calcium ion release than the other groups, however, with no statistically significant difference after 28 days (p > 0.05); and the largest inhibition halos for all strains, with no significant difference (E. coli and E. faecalis) for pure EB and EB + Bi2O3 (p > 0.05). EB presented similar performance to that of MTA as regards pH and calcium ion release; however, when ZnO and ZrO2 were used, EB did not present antimicrobial activity against some strains.